Otolith mass asymmetry in the adult indian mackerel Rastrelliger kanagurta (Cuvier, 1816), collected from the Sea of Oman - Jawad, Laith A. (2019)
The otolith mass asymmetry, x, was calculated as the difference between the mass of the right and left paired otoliths divided by average otolith mass. Saccular otolith mass asymmetry was studied in the pelagic water teleost Rastrelliger kanagurta. As in the case of other symmetrical fish species, the absolute value of x in R. kanagurta does not depend on fish length and otolith growth rate, although the absolute value of otolith mass difference is increased with the fish length. The value of x was between -0.2 and +0.2.